1998
DOI: 10.1200/jco.1998.16.4.1420
|View full text |Cite
|
Sign up to set email alerts
|

Costs of care associated with non-small-cell lung cancer in a commercially insured cohort.

Abstract: The direct health care costs of younger NSCLC patients care are substantial. These results should serve as a benchmark for future comparisons as the United States market shifts to managed care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 11 publications
1
23
0
Order By: Relevance
“…The healthcare costs associated with NSCLC are substantial [13,14]. Numerous studies have demonstrated that chemotherapy, including the novel chemotherapy regimens, represent cost-effective interventions relative to best supportive care in the treatment of patients with advanced NSCLC [15][16][17][18][19] Combination chemotherapy also appears to be cost-effective relative to monotherapy in such patients [20,21] However, there are few pharmacoeconomic data comparing the relative costs between novel chemotherapy agents.…”
Section: Discussionmentioning
confidence: 99%
“…The healthcare costs associated with NSCLC are substantial [13,14]. Numerous studies have demonstrated that chemotherapy, including the novel chemotherapy regimens, represent cost-effective interventions relative to best supportive care in the treatment of patients with advanced NSCLC [15][16][17][18][19] Combination chemotherapy also appears to be cost-effective relative to monotherapy in such patients [20,21] However, there are few pharmacoeconomic data comparing the relative costs between novel chemotherapy agents.…”
Section: Discussionmentioning
confidence: 99%
“…VCR data were collected from a chart audit of initial treatment and planned subsequent treatment, and included pathologic confirmation. This merged file (n ϭ 2542) was refined by excluding the following cases: small cell lung carcinoma (470), no subsequent claims within 1 year of diagnosis (19), limited insurance (167) or secondary insurance (age Ͻ 64) only (110), or assorted claims anomalies (70). The final sample of 1706 was stratified into 2 groups: those age Ͻ 64 years and those age Ն 65 years.…”
Section: Generating the Samplementioning
confidence: 99%
“…In the United States, in a cohort from a group medicine company, the mean cost of patients with non-small cell lung cancer over as timeframe of up to 12 months was US$ 40,485. 8 In relation to laryngeal cancer, radiotherapy and hospitalization were the main cost drivers in our hospital. The analysis by Van Agthoven et al 22 in the Netherlands also identifi ed that hospitalization was an important cost driver, and treatment for patients with primary tumors reached a mean of US$ 28,769 in a cohort of patients followed up for two years.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have estimated the hospital cost of lung, laryngeal and esophageal cancer in developed countries like the Netherlands, Switzerland, Canada, United States and United Kingdom. 1,6,8,16,22,23 Direct comparison between the results from the present study and these surveys is possible, although limitations relating to the heterogeneity of the methods used and the specifi c features of hospital care in the different healthcare systems need to be taken into consideration. The amounts in euros and pounds in the European studies were transformed into dollars using the exchange rates of 2006.…”
Section: Discussionmentioning
confidence: 99%